Implementation of e-crm (electronic customer relationship management) in improving the quality of service at 3 Saudara motorcycle wash - Amran, Ali; Muawanah, Siti; Wati, Mala Ayu Setia; Nisa, Yustia Fitrotul; Aprilia, Wahyu Nur (Jurnal Mandiri IT, 2025)
The purpose of this research effort is to critically examine the application of electronic customer relationship management (E-CRM) practices in improving service quality in Micro, Small, and Medium Enterprises (MSMEs). The methodological approach of this research is qualitative, using data collection techniques such as observation, interviews, and data collection. shows that the implementation of E-CRM can improve service quality through features such as online reservations, customer data management, and feedback systems. Key findings show that E-CRM facilitates queue management, speeds up service processes, and increases customer loyalty. The implications of this study highlight the importance of technology-based customer relationship management for SMEs to increase competitiveness and customer satisfaction.